The establishment of electoral law in revolutionary France - Filipiak, Zbigniew; Kowalczyk, Tomasz (Studia Iuridica Toruniensia, 2020)
The process of developing modern electoral law begins with the fundamental changes of the political system that occurred as a result of the outbreak of the French Revolution. The article shows the breakthrough moment – the resurrection of the Estates General, the fight for a fairer third estate representation system – (the bourgeoisie and the peasants represented 96% of the nation) and then the creation of a new census suffrage system that effectively suppressed the hopes of radical democrats. The concept of active and passive citizenship, developed by Emmanuel- Joseph Sieyes, consolidated the political achievements of the bourgeoisie and was adopted in the first constitution of France in 1791.